2020
DOI: 10.3390/en14010084
|View full text |Cite
|
Sign up to set email alerts
|

NO Formation and Autoignition Dynamics during Combustion of H2O-Diluted NH3/H2O2 Mixtures with Air

Abstract: NO formation, which is one of the main disadvantages of ammonia combustion, was studied during the isochoric, adiabatic autoignition of ammonia/air mixtures using the algorithm of Computational Singular Perturbation (CSP). The chemical reactions supporting the action of the mode relating the most to NO were shown to be essentially the ones of the extended Zeldovich mechanism, thus indicating that NO formation is mainly thermal and not due to fuel-bound nitrogen. Because of this, addition of water vapor reduced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(11 citation statements)
references
References 39 publications
0
11
0
Order By: Relevance
“…The latter is simply the result of the much lower inlet temperature used (320 K) which is 31% lower than the one used with the glow plug approach. The notable decrease of the maximum temperature is important because as was reported in the earlier work of Khalil et al 50 the NO production largely depends on the thermal NO mechanism. This justifies the significant decrease of NOx production displayed in Table 3, where it is shown that the addition of hydrogen peroxide leads to a 52% decrease in NOx.…”
Section: Resultsmentioning
confidence: 64%
See 2 more Smart Citations
“…The latter is simply the result of the much lower inlet temperature used (320 K) which is 31% lower than the one used with the glow plug approach. The notable decrease of the maximum temperature is important because as was reported in the earlier work of Khalil et al 50 the NO production largely depends on the thermal NO mechanism. This justifies the significant decrease of NOx production displayed in Table 3, where it is shown that the addition of hydrogen peroxide leads to a 52% decrease in NOx.…”
Section: Resultsmentioning
confidence: 64%
“…It is noted that the two-stage ignition exhibited herein is a feature introduced due to the addition of hydrogen peroxide as ammonia as a sole fuel exhibits single stage ignition. 50,51 Consequently, the first stage ignition is instrumental to the control of the whole ignition process as it can lead to qualitatively different outcomes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The contribution of the k-th process (chemical or transport) to the amplitude of the n-th mode can be assessed by the amplitude participation index (API) tool (P n k ) [77][78][79][80]:…”
Section: Methodsmentioning
confidence: 99%
“…The signs of the eigenvectors α i , β i are properly adapted in order to ensure that the amplitudes of all slow (active) modes are positive. The positive API values then indicate that the associated processes enhance the impact of the respective mode while the opposite holds for negative API values [103,104].…”
Section: Computational Singular Perturbation (Csp) and Its Algorithmi...mentioning
confidence: 99%